Activation of the aryl hydrocarbon receptor is the major toxic mode of action of an organic extract of a reference urban dust particulate matter mixture: the role of polycyclic aromatic hydrocarbons - Andrysík, Zdeněk; Vondráček, Jan; Marvanová, Soňa; Ciganek, Miroslav; Neča, Jiří; Pěnčíková, Kateřina; Mahadevan, Brinda; Topinka, Jan; Baird, William M; Kozubík, Alois; Machala, Miroslav (Mutation research, 2011)
Many of the toxic and carcinogenic effects of urban air pollution have been linked to polycyclic aromatic hydrocarbons (PAHs) adsorbed to airborne particulate matter (PM). The carcinogenic properties of PAHs in complex organic mixtures derived from PM have been chiefly attributed to their mutagenicity. Nevertheless, PAHs are also potent activators of the aryl hydrocarbon receptor (AhR), which may contribute to their nongenotoxic effects, including tumor promotion. As the genotoxicity of carcinogenic PAHs in complex mixtures derived from urban PM is often inhibited by other mixture constituents, the AhR-mediated activity of urban PM extracts might significantly contribute to the carcinogenic activity of such mixtures. In the present study, we used an organic extract of the urban dust standard reference material, SRM1649a, as a model mixture to study a range of toxic effects related to DNA damage and AhR activation. Both the organic extract and its neutral aromatic fraction formed a low number of DNA adducts per nucleotide in the liver epithelial WB-F344 cells model, without inducing DNA damage response, such as tumor suppressor p53 activation and apoptosis. In contrast, we found that this extract, as well as its neutral and polar fractions, were potent inducers of a range of AhR-mediated responses, including induction of the AhR-mediated transcription, such as cytochrome P450 1A1/1B1 expression, and the AhR-dependent cell proliferation. Importantly, these toxic events occurred at doses one order of magnitude lower than DNA damage. The AhR-mediated activity of the neutral fraction was linked to PAHs and their derivatives, as polychlorinated dibenzo-p-dioxins, dibenzofurans and biphenyls were only minor contributors to the overall AhR-mediated activity. Taken together, our data suggest that more attention should be paid to the AhR-dependent nongenotoxic events elicited by urban PM constituents, especially PAHs and their derivatives.
Keywords: poškození DNA; Receptors, Aryl Hydrocarbon; Genes, p53; adukty DNA; Rats; Dose-Response Relationship, Drug; mutageny; játra; DNA Adducts; polycyklické aromatické uhlovodíky; cytochrom P-450 CYP1A1; geny p53; Organic Chemicals; Polycyclic Aromatic Hydrocarbons; apoptóza; Apoptosis; pevné částice; DNA Damage; Mutagens; Cell Proliferation; Cytochrome P-450 CYP1A1; Liver; Animals; organické látky; Cell Line; proliferace buněk; zvířata; krysa rodu Rattus; receptory aromatických uhlovodíků; Particulate Matter; buněčné linie; vztah mezi dávkou a účinkem léčiva